As configurações subjetivas da participação política dos dirigentes partidários no PSDB/ES - Meira, Everton Faria (2013)
In PSDB decisions are centralized in the executive level and are members of the directorate who are not feel, themselves, party leaders. Therefore it is understood that in an adverse context, the PSDB has particularities relevant to the study of subjectiv